Culture interaction in South Asia : a historical perspective - Tirmizi, S. A. I., 1924-; Hamdard Institute of Historical Research; International Colloquium on Cultural Interaction in South Asia in Historical Perspective (1991 : New Delhi, India) (New Delhi : Hamdard Institute of Historical Research, 1993)
Papers and proceedings of the International Colloquium on Cultural Interaction in South Asia in Historical Perspective at New Delhi from 8 to 10 November 1991.
Includes bibliographical references and index.
Keywords: South Asia -- Civilization -- Congresses